Routine health check-ups for adolescents in Mwanza City, Tanzania: stakeholders' recommendations on its content, venue, and mode of delivery - Yovitha Sedekia; Gerry Mshana; Mussa K. Nsanya; Kid Kohl; Mwita Wambura; Heiner Grosskurth; David A. Ross; Saidi Kapiga (BMC, 2023)
Abstract Background Routine adolescent health screening aiming at the detection of unnoticed medical problems may increase awareness among policy makers and contribute to improved health in this population. Research is needed to inform the World Health Organization (WHO) and national health programs to provide evidence-based guidance on whether public health systems should offer comprehensive adolescent health screening, what should be included in different contexts, and how it should be delivered. We conducted formative research to define the content and delivery strategies for health check-ups to be performed in young (10-14 years) and older (15-19 years) adolescents, and to assess whether such services are likely to be acceptable and feasible in Tanzania. Methods As part of a collaborative research program coordinated by WHO in Chitungwiza, Zimbabwe; Mwanza City, Tanzania; and Cape Coast, Ghana a series of key informant interviews were conducted from April to July 2020, using a semi-structured guide with purposively selected stakeholders from government departments, non-governmental and community-based organisations, schools and health facilities. Data transcripts were coded using NVivo 12 software and thematic analysis was performed. Results We report results from 31 key informant interviews to address four main domains: proposed health conditions for routine health check-ups, health interventions to be combined with such check-ups, preferable venues, and the mode for delivering such screening activities. Stakeholders were supportive of introducing routine health check-ups among adolescents. They recommended focusing on non-communicable diseases, physical disabilities, common mental health problems, reproductive health problems, specific communicable diseases, and hygiene-related problems. They also recommended combining counselling and family planning information with these check-ups. Three venues were proposed: schools, community settings (to reach out-of-school adolescents), and youth-friendly health facilities (for conditions requiring a high level of confidentiality). Conclusions Stakeholders were supportive of the proposed routine health check-ups for adolescents, recommending specific health conditions to be screened for in both community and school settings. Based on the above, we plan to conduct implementation research to determine the number of new treatable conditions detected, and the costs of offering such services. In the longer term, evaluation of their health impact and cost-effectiveness will be required to guide policy.